Locust control update - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
During the growing season of 1995 further field trials using the fungus Metarhizium flavoriride to control locusts and grasshoppers have been carried out in several regions of Africa. (See Spore 55 p 1).